IDENTIFIKASI DERAJAT KEPENTINGAN KOMPONEN BANGUNAN DALAM MANAJEMEN PEMELIHARAAN DAN PERAWATAN BANGUNAN - Nico, Muhamad; Andayani, Relly (Universitas Gunadarma, 2014)
Rapid decline in quality of infrastructure assets as a result of factors such as age and environmental factors. So some developing asset management systems such as building condition assessment, prediction of deterioration, maintenance and treatment strategies, improvement of the condition after treatment and priority to building components should be repaired with cost barriers (Ahluwalia, 2008). The degree of interest of building components needed to incorporate the need for maintenance and upkeep of the building. The research method using a questionnaire with a scale degree of interest 1 (less important) to 6 (of extraordinary importance) (Pedro, et al, 2008). Statistical test research data using Friedman test and Kruskal Wallis. The results showed the component with the highest degree of interest is the structure components such as foundations, columns and beams with a degree of interest